People, Museums and the Rhetoric of Temporality: Considerations Regarding the Formation of the Collection at The Museum of Anthropology of Vancouver - Emanuela Rossi (Archivio Antropologico Mediterraneo)
In this article I went back to my doctoral research to show, through the analysis of archival material, how the Museum of Anthropology in Vancouver, a majority museum, according to Clifford's definition, turned from “savior” to “patron” in relation to indigenous artifacts and became trough the years, starting with the direction of Michael Ames (1974-97 and 2002-04), an international benchmark for collaborative approach in museums. This article, focusing on the 1950s and 1960s, still shows the outcomes of a salvage anthropology and the idea of disappearing cultures, although in the 1960s the idea of new and original indigenous productions begins to make its way. Since Clifford first visited the museum in the 1990s, significant changes have occurred. In the early 2000's the MOA received funding for the implementation of a new type of collaborative research, the Reciprocal Research Network (RRN), in which research is determined by the interests of the Indigenous communities rather than the museum or scholars.